2020
DOI: 10.1111/febs.15617
|View full text |Cite
|
Sign up to set email alerts
|

Alternative systems for misfolded protein clearance: life beyond the proteasome

Abstract: Protein misfolding is a major driver of ageing‐associated frailty and disease pathology. Although all cells possess multiple, well‐characterised protein quality control systems to mitigate the toxicity of misfolded proteins, how they are integrated to maintain protein homeostasis (‘proteostasis’) in health—and how their disintegration contributes to disease—is still an exciting and fast‐paced area of research. Under physiological conditions, the predominant route for misfolded protein clearance involves ubiqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 206 publications
(306 reference statements)
3
50
0
Order By: Relevance
“…By contrast, the larger ubiquitin-and SQSTM1-positive inclusions were also positive for LC3-II (Figure 5B, white). Furthermore, we observed that the aggregates were dispersed throughout the cytosol of Cd-treated cells, in sharp contrast to juxtanuclear aggresomes reported for misfolded proteins [65]. Similarly, Cd led to disruption of the mitochondrial network (labeled with MitoTracker dye, magenta), which was concentrated at the site of SQSTM1 aggregates (Figure 6A,B, blue), consistent with the fact that SQSTM1 is an autophagy receptor for mitochondria.…”
Section: Inhibition Of the Degradation Of Three Selective Autophagy Substrates-sqstm1 Ubiquitinated Proteins And Mitochondria By CDsupporting
confidence: 74%
“…By contrast, the larger ubiquitin-and SQSTM1-positive inclusions were also positive for LC3-II (Figure 5B, white). Furthermore, we observed that the aggregates were dispersed throughout the cytosol of Cd-treated cells, in sharp contrast to juxtanuclear aggresomes reported for misfolded proteins [65]. Similarly, Cd led to disruption of the mitochondrial network (labeled with MitoTracker dye, magenta), which was concentrated at the site of SQSTM1 aggregates (Figure 6A,B, blue), consistent with the fact that SQSTM1 is an autophagy receptor for mitochondria.…”
Section: Inhibition Of the Degradation Of Three Selective Autophagy Substrates-sqstm1 Ubiquitinated Proteins And Mitochondria By CDsupporting
confidence: 74%
“…The cytosol is a prominent location for the subcellular quarantine of misfolded proteins. Numerous QC compartments have been described in yeast and mammals including the juxta-nuclear QC compartment (JUNQ) and insoluble protein deposit (IPOD) as well as the intranuclear QC compartment (INQ), stress granules, Q-bodies, p62 bodies and aggresome-like induced structures (reviewed in [ 104 ] and [ 105 ]). These compartments are by no means static as there is evidence of protein exchange between JUNQ and INQ [ 106 ], instead they act as molecular intersections with chaperones, UPS components and the autophagy machinery all converging here to triage damaged proteins.…”
Section: Compartmentalisation and Phase Separationmentioning
confidence: 99%
“…The K48-linked polyubiquitin chain delivers target substrates to the proteasome, where ubiquitinated target substrates are degraded in an ATP-dependent manner [61,62]. In contrast, the K63-linked polyubiquitin chain is largely involved in non-proteolytic functions, such as DNA damage repair, cellular signaling, aggresome formation, and ribosome biogenesis [63][64][65][66].…”
Section: The Ubiquitin-proteasome Systemmentioning
confidence: 99%